Crowd management strategies and safety performance among sports tourism event venue organizers in Kuala Lumpur and Selangor - Rahmat, Norazlina; Jusoff, Kamaruzaman; Ngali, Norzaidah; Ramli, Noorazlin; Md. Zaini, Zetty Madina; Samsudin, Azlina; Abd Ghani, Fatimah; Hamid, Munirah (IDOSI Publications, 2011)
High risk of injuries and accidents among attendees at event, especially Sports Tourism Event has become one of the major concerns to researchers and practitioners. One of the major strategies to ensure attendees safety is by practicing effective crowd management strategies. The aim of this study was to investigate the level of crowd management strategies and safety performance practices among sports tourism event venue organizers in Kuala Lumpur and Selangor, Malaysia. The sample included 40 of safety or operation manager attached to sports tourism event venue organizers. The results of the statistical analysis revealed that the correlation crowd management strategies had significant relationship with safety performance. Since the findings may not have utilitarian value to other event venues in Malaysia, future studies might consider using a national sample rather than the local sample.